Exploring the link between traffic violations and moral disengagement: A scoping review - Haouria Basiyd-Fellahi; Patricia Delhomme; Julien Cestac (Transportation Research Interdisciplinary Perspectives)
Traffic violations are a major contributor to road traffic crashes. It is therefore imperative to understand why motorists commit traffic violations. Some studies have identified the use of self-exonerating strategies, such as Moral Disengagement (MD; Bandura, 1990), as a contributing factor to this decision-making process. The present scoping review aims to provide a comprehensive overview of current research on the relationship between MD and traffic violations, evaluate the methodologies used to measure road-specific MD, and identify gaps in the literature to inform future research. Seventeen articles were identified in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline extension for Scoping Reviews. PsycINFO and SCOPUS databases were searched for articles published between 2000 and 2023. This scoping review revealed several key findings: a) only two articles explicitly addressed and measured MD, while the remaining 15 employed measures implying MD without explicitly addressing it; b) a positive relationship between MD and traffic violations was found, with evidence suggesting an additional positive link between anger and road-specific MD; and c) theoretical overlaps were identified between MD theory, the Theory of Planned Behaviour and the Model of Retaliatory Aggressive Driving. In light of these findings, it appears relevant to consider the role of MD in traffic violations when developing interventions to reduce them. However, further studies are required to better understand the observed relationship between MD and traffic violations and the role of emotions in this process. This step is necessary to provide a more informed basis for road safety programmes.